Hadzic's peripheral nerve blocks and anatomy for ultrasound-guided regional anesthesia 2026-02-15T23:46:44+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from session cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Hadzic, Admir (McGraw-Hill Professional, 2012)

(untitled)
"Hadzic's Peripheral Nerve Blocks delivers practical, state-of-the-art guidance for all major nerve block procedures, including ultrasound-guided nerve blocks. A standardized,user-friendly presentation provides meticulous, step-by-step instructions for each procedure. The second edition has been completely updated to include new developments, the latest equipment, and hundreds of new photographs"--Provided by publisher